2020
DOI: 10.1016/j.heliyon.2020.e03374
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chronic brain protein changes and protein targets of serum auto-antibodies after blast-mediated traumatic brain injury

Abstract: In addition to needing acute emergency management, blast-mediated traumatic brain injury (TBI) is also a chronic disorder with delayed-onset symptoms that manifest and progress over time. While the immediate consequences of acute blast injuries are readily apparent, chronic sequelae are harder to recognize. Indeed, the identification of individuals with mild-TBI or TBI-induced symptoms is greatly impaired in large part due to the lack of objective and robust biomarkers. The purpose of this study was to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…Our results show that the jet-flow OPC, which has been widely used in experimental studies designed to model bTBI, [31][32][33][34][35][36][37][38][39][40][41] actually generates a powerful, collimated jet flow of very high dynamic pressure at the specimen location. Although the intensity of this jet flow decays over 18 msec as the Driver Section depressurizes, this exposure condition does not represent that of explosive blast or a traveling shockwave.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Our results show that the jet-flow OPC, which has been widely used in experimental studies designed to model bTBI, [31][32][33][34][35][36][37][38][39][40][41] actually generates a powerful, collimated jet flow of very high dynamic pressure at the specimen location. Although the intensity of this jet flow decays over 18 msec as the Driver Section depressurizes, this exposure condition does not represent that of explosive blast or a traveling shockwave.…”
Section: Discussionmentioning
confidence: 76%
“…This model may be termed multi-modal TBI (mmTBI), with the caveat that this is purely a descriptive term for the experimental condition, and not a term that is currently used in clinical diagnosis of human TBI. We note, however, that this model is clearly capable of inducing neurotrauma [31][32][33][34][35][36][37][38][39][40][41] and may be considered useful for studying brain cell processes after injury and in evaluating the efficacy of putative therapeutic agents. For example, through this mmTBI model we have recently reported the unexpected ability to reverse chronic neurodegeneration in the brain and restore neurological function at a very distal time-point (over 1 year) after TBI in mice, challenging the long-held dogma that the treatment window for saving brain tissue from chronic degeneration and impaired cognitive functioning is limited to an acute time period immediately following injury.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ribosomal defects can lead to elevated ROS and activation of the TP53 pathway, which have important links with TBI (Sulima et al, 2019 ). The differential expression of RPL27 and RPS15A was validated in TBI mice (Harper et al, 2020 ). Recent studies have shown that RPL7 and RPL23A are differentially expressed in senile dementia and may be potential biomarkers (Shigemizu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have studied this chronic condition in a murine model of multimodal TBI (mmTBI) that entails jet-flow exposure in an overpressure chamber to produce globally compressive forces along with a variable amount of acceleration–deceleration and early blast wave exposure. This laboratory model produces neurodegeneration and neurobehavioral deficits reminiscent of TBI in people ( 21 24 ). We treated and analyzed mice beginning 1 y after a single injury, as outlined in Fig.…”
mentioning
confidence: 99%